A COMPREHENSIVE ANALYSIS OF LEARNING STYLES AND THEIR IMPACT ON EDUCATION - Davronova Marjona Sherzod qizi (TADQIQOTLAR, 2025)
Abstract. This article explores the concept of learning styles and their impact on education. It examines various models, including VARK, Gardner’s Multiple Intelligences, and Kolb’s Experiential Learning Theory. Through a detailed analysis of research methodologies, the study highlights how different learning preferences influence academic performance. This also discusses statistical and algorithmic approaches used to identify learning styles. The findings suggest that while individualized learning approaches can enhance student engagement and success, a flexible teaching strategy is most effective.